T cells, natural killer cells, and γδT cells in a large patient cohort with rheumatoid arthritis: influence of age and anti-rheumatic therapy. (2nd January 2020) - Schwaneck, EC; Renner, R; Junker, L; Tony, H-P; Kleinert, S; Gernert, M; Schmalzing, M; Gadeholt, O
Abstract : Objective : The aim of this cohort study was to evaluate the distribution of natural killer (NK) cells and T-cell subsets, including γδT cells, in the peripheral blood of patients with rheumatoid arthritis (RA) in a large real-life patient cohort, taking into account the patients' demographics, disease characteristics, and anti-rheumatic therapy. Method : The study recruited 508 RA patients between November 2013 and August 2015. Lymphocyte differentiation using eight-colour flow cytometry (fluorescence-activated cell sorting) of the peripheral blood was performed for all patients. Clinical data, including age, gender, disease duration, serostatus, disease activity, antibody status, immunosuppressive therapy including use of different biological disease-modifying anti-rheumatic drugs (bDMARDs) and conventional synthetic DMARDs, were retrospectively assessed using electronic patient files. Multivariate regression analysis was performed to assess the effect of these variables on T-cell, NK-cell, and γδT-cell counts. Results : The median patient age was 61.0 years and 74.1% were female. The median disease duration of RA was 12.0 years. Median Disease Activity Score based on 28-joint count was 2.8 and 56.3% were treated with bDMARDs. There were no differences in immunosuppressive therapy between different age groups. While rituximab, abatacept, and tocilizumab had no influence on lymphocyte subdifferentiation, tumour necrosis factor (TNF) inhibitors and age significantly influenced the numbers of T cells, T-helper cells, T-NK cells, NK cells, and γδT cells. Conclusion : Age and TNF-inhibition therapy influence lymphocyte subdifferentiation in patients with RA. It may be prudent to use age- and therapy-adjusted standard values for lymphocyte subsets during clinical trials and treatment of RA.